Heterojunction Nanomedicine. Issue 11 (17th February 2022) - Pan, Chao; Mao, Zhuo; Yuan, Xue; Zhang, Hanjie; Mei, Lin; Ji, Xiaoyuan
Abstract: Exogenous stimulation catalytic therapy has received enormous attention as it holds great promise to address global medical issues. However, the therapeutic effect of catalytic therapy is seriously restricted by the fast charge recombination and the limited utilization of exogenous stimulation by catalysts. In the past few decades, many strategies have been developed to overcome the above serious drawbacks, among which heterojunctions are the most widely used and promising strategy. This review attempts to summarize the recent progress in the rational design and fabrication of heterojunction nanomedicine, such as semiconductor–semiconductor heterojunctions (including type I, type II, type III, PN, and Z–scheme junctions) and semiconductor–metal heterojunctions (including Schottky, Ohmic, and localized surface plasmon resonance–mediated junctions). The catalytic mechanisms and properties of the above junction systems are also discussed in relation to biomedical applications, especially cancer treatment and sterilization. This review concludes with a summary of the challenges and some perspectives on future directions in this exciting and still evolving field of research. Abstract : This review summarizes the recent progress in the rational design and fabrication of heterojunction nanomedicine. The catalytic mechanisms and properties of applied heterojunction systems are also discussed in relation to biomedical applications, especially cancer treatment and sterilization. This review concludes with a summary of the challenges and perspectives on future directions in this evolving field of research.